Community structure of macrozoobenthic feeding guilds in responses to eutrophication in Jakarta Bay - AM AZBAS TAURUSMAN (Biodiversitas Journal of Biological Diversity, 2010)
Taurusman AA (2010) Community structure of macrozoobenthic feeding guilds in responses to eutrophication in Jakarta Bay.Biodiversitas 11: 133-138. The group of benthic fauna which feed on the same food sources are classified as a feeding guild. The objective of the present study was to evaluate the distribution and composition of macrozoobenthic feeding guilds along gradient of organic enrichment (trophic states) in Jakarta Bay. The result of the present study was shown that at the hypertrophic stations of the bay dominated by species of surface deposit feeding polychaetes such as, Dodecaceria sp., Cirratulus sp., Capitella sp., and Spionidae. The eutrophic zone of the bay was dominated by suspension feeding bivalves Mactra sp., Chione sp. The offshore area (mesotrophic zone)showed a high diversity of species and feeding guilds compared to other areas. The patterns of feeding guilds in the mesotrophic zone indicated a higher stability of macrozoobenthos community, indicated by the presence of deep-deposit feeder (e.g. Acetes sp.), surface deposit feeders (e.g. Prionospio sp.), suspension feeders (e.g. Chione sp.), and carnivores (e.g. Nephthys sp.) in comparable proportions.The structure of macrozoobenthic feeding guilds in an eutrophic coastal water is positively related to the quantity and quality of organic matters (eutrophic states), and the capability of benthic species in adaptation to such environmental condition.Key words: macrozoobenthos, feeding guild, eutrophication, coastal water, Jakarta Bay.